2021
DOI: 10.2176/nmc.tn.2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

A Super-selective Wada Test Successfully Detected an Artery That Supplied Broca’s Area in a Case of Left Frontal Lobe Glioblastoma: Technical Case Report

Abstract: In cases of malignant gliomas located at language eloquent area, it is often difficult to preoperatively detect those area with functional MRI. Awake surgery is often used to spare the language eloquent area during surgery for such tumors; it is not available for a patient whose intracranial pressure is elevated due to the malignant tumor. The Wada test involves infusing anesthetic agents into the internal carotid artery to determine language dominancy before surgery for epilepsy or brain tumor. The super-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The ssWada method is less invasive than ECS mapping and can evaluate within-hemisphere distribution of higher cognitive functions. Yamashita et al (2021) . reported a case in which fMRI hardly identified Broca's area, but ssWada successfully revealed a language area in the frontal lobe and achieved tumor resection without language impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ssWada method is less invasive than ECS mapping and can evaluate within-hemisphere distribution of higher cognitive functions. Yamashita et al (2021) . reported a case in which fMRI hardly identified Broca's area, but ssWada successfully revealed a language area in the frontal lobe and achieved tumor resection without language impairment.…”
Section: Discussionmentioning
confidence: 99%
“…can efficiently assess language function and reduce complications related to intracarotid propofol injection. In parallel to this invention, some papers have reported cases in which selective anesthetic infusion into the cerebral artery branch contributed to the prediction of postoperative complications ( Hajek et al, 1998 , Urbach et al, 2002 , Yamashita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 The ssWada has advantages in selectivity and the avoidance of consciousness disturbance in patients with malignant glioma in the left inferior frontal gyrus. 7 Functional mapping by ECS can directly evaluate the regional functions of the brain using intracranial electrodes [28][29][30] or awake craniotomy. 31,32 However, the evaluation is based on the limited volume of ECS.…”
Section: Observationsmentioning
confidence: 99%
“…5 We previously developed the superselective Wada (ssWada) to evaluate voluntary functions in specific brain regions by the superselective infusion of an anesthetic agent from the intracranial artery. 6,7 The ssWada can induce a focal neurological deficit corresponding to the area perfused by the selected artery without inducing unwanted consciousness disturbance, which mainly results from unintended distribution to perforating arteries. Consequently, the subject can directly explain their experience and symptoms, which provides a more accurate simulation of likely postsurgical neurological symptoms.…”
mentioning
confidence: 99%
“…Fujii et al [ 1 ] suggested that selective anesthetic infusion into the middle cerebral artery (MCA) reduces adverse effects in the Wada test. We established a modified version of the Wada test using super-selective catheterization that involves injecting anesthetics selectively into the target arteries corresponding to the planned resection area [ 3 , 16 ], named the “super-selective Wada test” (ssWada). As most of the brain areas responsible for language are perfused by the MCA, we believe that the ssWada in the MCA region will help adequately anesthetize language-related areas with minimal effect in adjacent regions, compared with the cWada.…”
Section: Introductionmentioning
confidence: 99%